2010
DOI: 10.3390/ijerph7124127
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Methodology to Evaluate Health Impacts Caused by VOC Exposures Using Real-Time VOC and Holter Monitors

Abstract: While various volatile organic compounds (VOCs) are known to show neurotoxic effects, the detailed mechanisms of the action of VOCs on the autonomic nervous system are not fully understood, partially because objective and quantitative measures to indicate neural abnormalities are still under development. Nevertheless, heart rate variability (HRV) has been recently proposed as an indicative measure of the autonomic effects. In this study, we used HRV as an indicative measure of the autonomic effrects to relate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…In our previous study, VOC exposure concentrations and HRV using VOC and Holter monitors were measured for seven healthy subjects [ 18 ]. In this study, we applied this method to MCS patients and identified characteristics of the relationship between VOC exposure, biological effects, and subjective symptoms in actual lives.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, VOC exposure concentrations and HRV using VOC and Holter monitors were measured for seven healthy subjects [ 18 ]. In this study, we applied this method to MCS patients and identified characteristics of the relationship between VOC exposure, biological effects, and subjective symptoms in actual lives.…”
Section: Introductionmentioning
confidence: 99%
“…Odor pollution usually causes serious annoyance in urban areas because of the pungent smell and health hazards [ 1 ]. Usually, the composition of odor pollutants and their concentrations are various in different fields.…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale exposure to VOCs causes ocular and throat irritation, vomiting, nausea, headache, loss of coordination, skin allergy [2][3][4], etc. Chronic effects that have been observed with VOCs include damage to the liver, lungs, kidney, reproductive system, respiratory system [5], and central nervous system in human beings. It is well known that some of the VOCs are carcinogenic [6,7] too.…”
Section: Introductionmentioning
confidence: 99%